Mitigasi Covid-19 Melalui Kearifan Lokal Pesantren di Madura - Abd Hannan; Heny Triyaningsih (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2020)
Abstract: This study discusses strategies to strengthen the global pandemic COVID-19 mitigation in Madura through the utilization of the local wisdom values ​​of pesantren. There are three focus issues raised in this study, namely; COVID-19, the value of local wisdom, and finally pesantren. Using this type of qualitative research based on an analysis of sociological theory, this study found that the pesantren's social position as one of Madura's local wisdom values ​​could actually be used as a strategy to strengthen the COVID-19 transmission and transmission control activities in Madura. The strengths and advantages of pesantren in strengthening COVID-19 mitigation in Madura can be seen from two things; First, pesantren is a popular traditional Islamic institution that is synonymous with magical power and charismatic clerical figures. With this, pesantren can be used as instruments to educate the public about the importance of complying with the health protocol regulations issued by the government; Secondly, pesantren have large and broad social capital, where the social capital is centered on three networks of power such as the kyai, santri, and aumni. In this regard, both the kyai, santri, and alumni, all three can be used to strengthen the COVID-19 control agenda in Madura, specifically to target some areas which have not been adequately addressed by formal policies. The involvement of pesantren and all their social networks such as kyai, santri, and alumni, besides being able to strengthen the COVID-19 mitigation agenda, can also realize an integral role control model by combining two approaches at once, namely structural approaches and value-based approaches of local wisdom.